2017
DOI: 10.1371/journal.pone.0178913
|View full text |Cite
|
Sign up to set email alerts
|

Effective strategies to motivate nursing home residents in oral care and to prevent or reduce responsive behaviors to oral care: A systematic review

Abstract: BackgroundPoor oral health has been a persistent problem in nursing home residents for decades, with severe consequences for residents and the health care system. Two major barriers to providing appropriate oral care are residents’ responsive behaviors to oral care and residents’ lack of ability or motivation to perform oral care on their own.ObjectivesTo evaluate the effectiveness of strategies that nursing home care providers can apply to either prevent/overcome residents’ responsive behaviors to oral care, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 99 publications
0
38
0
Order By: Relevance
“…Focusing on people with dementia, both Siegel et al and Rozas et al pointed out a lack of knowledge regarding effective methods to improve oral health, so no recommendations could be made concerning specific interventions. Two systematic reviews by Hoben et al and a review by Albrecht et al stressed the low quality of the available evidence and the need of rigorous studies using relevant outcome measures.…”
Section: Resultsmentioning
confidence: 99%
“…Focusing on people with dementia, both Siegel et al and Rozas et al pointed out a lack of knowledge regarding effective methods to improve oral health, so no recommendations could be made concerning specific interventions. Two systematic reviews by Hoben et al and a review by Albrecht et al stressed the low quality of the available evidence and the need of rigorous studies using relevant outcome measures.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have reported that oral hygiene and the health of the institutionalized elderly population, particularly in those with cognitive problems, are usually poor, which is attributed to a disregard for the need for oral healthcare among them and may also be due to the inadequate knowledge and skills, poor attitudes and improper practices of caregivers [96,97,99,100,101]. Oral care is usually not treated as a priority or a routine, resulting in delayed oral assessment and treatment [37,101,102]. The reasons for inadequate oral care practices among caregivers have been examined and were related to the following:time constraints and priority setting,insufficient education about oral care and skills,a lack of awareness regarding the importance of oral care in oral/dental diseases [103],an unwillingness to provide oral care due to the fear of managing uncooperative residents,the prevention of potential injuries, andavoiding an unpleasant task [104,105,106].…”
Section: Discussionmentioning
confidence: 99%
“…Community nurses can educate and empower older people to take an active role in their oral care to prevent oral problems [37]. Nurses working in residential communities can take a leadership role in ensuring oral health care is integrated into routine nursing care [38]. Nurses can screen each resident's oral health upon admission, assess the need for an examination by a dental professional, and prepare and monitor an oral health care plan [25,39,40].…”
Section: Rationalementioning
confidence: 99%